(untitled) (Лучшие интеллектуальные исследования, 2025)
Abstract. International labor migration is a defining global phenomenon of the 21st century, profoundly shaping economies and societies worldwide. This article offers a comprehensive analysis of the macroeconomic consequences of international labor migration, examining its multifaceted impacts on both migrant-sending and migrant-receiving countries. For sending countries, the discussion focuses on the critical role of remittances in boosting national income, poverty reduction, and investment, while also exploring the challenges of "brain drain" and its potential mitigation through "brain circulation" or "brain gain." We analyze the effects on labor markets, human capital development, and structural economic transformation. For receiving countries, the article investigates how migration influences labor supply, productivity, economic growth, and wage dynamics. It also addresses the fiscal impacts, innovation effects, and the broader challenges related to social integration and labor market segmentation. By highlighting both the significant economic benefits and the inherent complexities and challenges associated with international labor mobility, this paper underscores the necessity of well-managed, coherent, and inclusive migration policies to maximize positive outcomes and mitigate adverse consequences for all stakeholders involved.